Amplification in the Face of Adversity: Novel Therapeutic Approaches in the COVID-19 Pandemic: Novel Therapeutic Approaches in the COVID–19 Pandemic. (3rd April 2021) - Howe, Andrew John; Jones, Merryn
ABSTRACT: The COVID-19 pandemic has had far-reaching consequences for those from all walks of life around the globe. The practice of psychotherapy has been no different, with much work moving to video calls and online services. Therapeutic communities have particularly felt this change. In this article the authors report on how a therapeutic community in south London sought novel ways to work with patients during the pandemic. On reflection, they used aspects of analytical psychology, specifically amplification and an openness to arts in therapy, to good effect with one of their clients. In this article, the authors present this case covering the narrative of the therapeutic relationship, the artistic material created and worked with, followed by a consideration of what has taken place using Jung's amplification as a way of understanding, with the hope that it may provide an example of how analytical psychology can be used to find solutions to some of the issues raised by the COVID-19 pandemic.